Clarias insolitus, a new species of clariid catfish (Teleostei: Siluriformes) from southern Borneo - Ng, Heok Hee (Zootaxa, 2003)
A new species of catfish in the genus Clarias is described from the Barito River drainage in southern Borneo. Clarias insolitus can be clearly distinguished from all other Southeast Asian Clarias species in having a long and thin anterior fontanel and hypertrophied sensory canal pores on the head and body that are easily visible to the naked eye. Additional diagnostic characters not unique to this species are a uniform violet-gray color without any white spots on body and prominent serrations on the anterior edge of the pectoral spine.